TV Boxes as Support Servers for IoT Applications - Bannwart, Tiago Godoi; Luz, Gustavo P. C. P da; Sato, Gabriel Massuyoshi; Gonzalez, Luis Fernando Gomez; Borin, Juliana Freitag (Anais do Workshop on Sustainable Computing and Technology Reuse (SCoRe); 2025: Anais do I Workshop on Sustainable Computing and Technology ReuseDO - 10.5753/score.2025.17175, 2025)
This paper presents a fog computing server designed for Internet of Things (IoT) applications, which promotes the reuse of seized TV Box devices. A smart parking system deployed at the Institute of Computing, Unicamp served as the first IoT application to use the server with a TV Box model with limited hardware resources. The device was configured to provide monitoring services, enable remote firmware updates, and generate temporal metrics. Experimental results show that the system achieved operational stability, low energy consumption, and satisfactory performance within the proposed scenario. These findings confirm the technical feasibility of repurposing TV Boxes and highlight their potential as a low-cost and environmentally sustainable alternative for fog computing applications, in line with the principles of the circular economy.